Phytoremediated marine sediments as suitable peat-free growing media for production of red robin photinia (Photinia x fraseri). (June 2018) - Mattei, Paola; Gnesini, Alessandro; Gonnelli, Cristina; Marraccini, Chiara; Masciandaro, Grazia; Macci, Cristina; Doni, Serena; Iannelli, Renato; Lucchetti, Stefano; Nicese, Francesco P.; Renella, Giancarlo
Abstract: Sediments dredged by an industrial port, slightly contaminated by heavy metals and petroleoum hydrocarbons, were phytoremediated and used as peat-free growing media for the red robin photinia ( Photinia x fraseri L.). Plants were grown on sediment only (S), sediment mixed with composted pruning residues (S + PR), sediment fertilized with controlled release fertilizers (S + F) and peat-based growing media as control (C). Plant elongation and dry weight, leaf contents of chlorophyll, malondialdehyde (MDA), macronutrients and heavy metals were determined at the end of one growing season. Environmental impact related to the use of sediment-based as compared to peat-based growing media was assessed by the Life Cycle Analysis (LCA). Sediment-based growing media presented significantly higher bulk density, pH and electrical conductivity values, lower C and N contents, and significantly higher total and available P. Red robin photinia grown on S + F growing media showed morphological and chemical parameters similar to those of control plants (C), whereas plants grown on S and S + PR showed lower growth. Leaf concentration of nutrients and heavy metals varied depending on the considered element and growing media, but were all within the common values for ornamental plants, whereas the highest MDA concentrations were found in plants grown on traditional growing media. The LCA indicated the use of sediments as growing media reduced the C footprint of ornamental plant production and the contribute of growing media to the environmental impact per produced plant. We concluded that sediments phytoremediation and use in plant nursery is a practical alternative re-use option for dredged sediments. Highlights: Phytoremediated marine were used as peat-free growing media for growing red robin photinia plants. Environmental impact related to the use of sediments-common peat-based growing were compared by LCA. Plants grown on fertilized sediments were comparable to those grown on peat-based growing media. The LCA showed a lower C footprint of plants grown on sediment-than peat-based growing media.